Constructive-technological diagram of the rotary–string cultivator and the definition of its main parameters - Konovalov Vladimir; Konovalov Sergey; Igumnova Victoria (E3S Web of Conferences, 2019)
Organizing technological processes in accordance with adopted system of agriculture, producers of agricultural products tend to get maximum possible yield with minimizing costs and increasing the level of soil fertility. A fallow system is one of effective systems of soil processing for accumulation of nutrients and moisture, as well as weed control. Fallow cultivation of soil is used when using this system for weed control. First cultivation is carried out with help of fallow or continuous cultivators, which have low productivity and high energy intensity. To eliminate these shortcomings, authors proposed a structural and technological scheme of a rotor-lug cultivator, the main element of which is rotor-string working bodies on flexible shaft. Tillage rotary-string work by hauling leads to propelling-rotational effects. There were obtained analytical dependences for determining speed of string required for cutting stem of weeds under different physical-mechanical parameters of stem and soil, as well as technological indicators of a cultivator’ operation. The authors obtained expressions for determining the radius of string installation from axis of rotation, angle of section installation to the direction of motion of energy means, as well as the number of strings required for guaranteed cutting of weeds deeper than the point of growth.